Mono and bifunctional aromatic esterificated benzophenone photoinitiators for free radical polymerization - Aydin, Meral; Temel, Gokhan; Balta, Demet Karaca; Arsu, Nergis (SPRINGER, 2015)
Aromatic esterificated benzophenone derivatives, benzoic acid 4-benzoyl-phenyl ester (BPBz) and bis-benzoic acid 4-benzoyl-phenyl ester (BisBPBz) were simply synthesized and characterized. The triplet states of the photoinitiators were determined by laser flash photolysis and phosphorescence spectroscopy. The photodecomposition of the initiators was performed by UV light; the increase in the absorption spectra was attributed to the decreasing number of ester groups which led to an increase in ketone groups according to the Photo-Fries rearrangement of aromatic esters. The photoinitiation capabilities for methyl methacrylate (MMA) polymerizations were investigated under air and nitrogen atmospheres. Ester-functional benzophenone photoinitiators were found to be more effective than benzophenone (BP) in the presence of a co-initiator for photoinduced free radical polymerization of MMA. The kinetics of photopolymerization for different formulations which consist of multifunctional acrylates was also studied using the Real-Time Fourier Transform infrared spectroscopy (RT-FTIR) method. The film properties of these formulations were investigated after curing of films by Mini-UV-Cure equipment.
Keywords: Benzophenone; Free radical polymerization; Photo-fries rearrangement; Type II system; UV curing; CLICK CHEMISTRY; THIOXANTHONE; INITIATOR; PHOTOPOLYMERIZATION; ESTERS; Polymer Science